Sistema GPS: uma órbita em evolução - número de satélites e periodicidade - Brito, Gustavo Reis de [UNESP]; Corrêa, Caroline dos Santos [UNESP]; Bongiovanni, Solange [UNESP]; Rodrigues, Ramon Juliano [UNESP] (EIA Energy in Agriculture, 2014)
The objective of this project was to monitor the satellites of the Global Positioning System (GPS) from a fixed point on Earth and to verify the rate of recurrence respect to their rotation and displacement. A topographic GPS signal receiver connected to a personal computer was used to recorded, for five days, the displacement of the satellites. This work was based on the fact that many literature references state that satellites complete one orbit around the Earth every 12 hours, then, it is assumed that the satellite would be seen twice in a day from the same fixed point on Earth.Although, this does not occur, as thise time interval correspond to 12 hours sidereal time and not solar time. In addition, this study was carried out in order toconfirm and update the information related to the number of satellites in operation today, found to be 31. In that sense, some references concerning the space segment of this system were defined in details.

O presente artigo teve como objetivo monitorar os satélites do Sistema de Posicionamento Global (GPS) a partir de um ponto fixo na Terra e verificar a periodicidade desses quanto a sua rotação e deslocamento. Para a realização desse monitoramento foi utilizado um receptor topográfico de sinal GPS conectado a um computador que registrou durante cinco dias o deslocamento dos satélites. A motivação desse trabalho se deu pelo fato de que muitas referências ao afirmar que os satélites completam uma volta em torno da Terra a cada 12 horas, supõe-se então que um determinado satélite poderia ser visto duas vezes por dia de um mesmo ponto fixo na Terra, o que não ocorre, haja vista que essas 12 horas correspondem ao tempo sideral e não solar. Verificou-se também o número de satélites do sistema GPS, visando atualizar as informações relacionadas aos satélites em operação que hoje tem em funcionamento 31 satélites do sistema GPS conforme descrito.
GPS: an orbit evolution - number of satellites and periodicity
Keywords: Sidereal time; Satellite monitoring; Satellite space segment; Hora sideral; Monitoramento de satélites; Segmento espacial